Cystic fibrosis: desensitization in delayed hypersensitivity reactions to elexacaftor/tezacaftor/ivacaftor - Gómez-Ganda, L.; Galván-Blasco, P.; Fernández-Polo, A.; Cardona, V.; García-Palop, B.; Parramón-Teixidó, CJ; Polverino, E.; Álvarez-Fernández, A. (Frontiers in Pharmacology, 2024)
Background. Cystic fibrosis transmembrane conductance regulator modulators are the only available treatment for cystic fibrosis. Although elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) is well-tolerated, rash has been reported as very frequent. In severe rashes, ELX/TEZ/IVA withdrawal is necessary, leading to clinical deterioration. The objective of the study is to increment the experience of ELX/TEZ/IVA desensitization. Methods. Adult patients who developed a delayed hypersensitivity rash to ELX/TEZ/IVA between December 2021 and February 2023 and required withdrawal due to ineffective rescue medication were included. Skins test for ELX/TEZ/IVA and IVA were conducted to establish hypersensitivity mechanism. Balijepally ELX/TEZ/IVA desensitization protocol was selected. In cases where desensitization had to be discontinued due to rash, an extended desensitization was proposed. Clinical and health-related quality of life parameters were collected before ELX/TEZ/IVA and after desensitization. Results. 162 patients (81 women, 31.2 [23.8-42.5] years) started ELX/TEZ/IVA, developing rash 12 of them (7.4%, six women). Six patients (five women) required stopping ELX/TEZ/IVA and were selected for desensitization. Skin tests indicated delayed type-IV hypersensitivity in one patient. Two patients presented adequate tolerance to desensitization; while, four patients developed rash. Three of these patients, successfully concluded extended desensitization (one patient declined participation). No significant clinical deterioration or quality of life worsening was observed during desensitization; in fact, there was an improvement in practically all measured parameters. All five patients who resumed ELX/TEZ/IVA are currently receiving therapy with good tolerance. Conclusions. Desensitization to ELX/TEZ/IVA could be a successful and safe strategy for reintroducing this essential treatment in cases of a delayed hypersensitivity rash.